Impact of age on the diagnostic performance of unstimulated salivary flow rates and salivary gland ultrasound for primary Sjögren's syndrome - Lee, Kyung-Ann; Kim, Se-Hee; Kim, Hae-Rim; Kim, Hyun-Sook (Frontiers in Medicine, 2022)
Background: Age-related changes and different patterns of salivary gland abnormalities according to age may affect the diagnostic performance of unstimulated salivary flow rate (USFR) and salivary gland ultrasound (SGUS) for primary Sjögren’s syndrome (pSS). We aimed to evaluate the threshold and diagnostic performance of USFR and whether incorporating SGUS or replacing USFR with SGUS affects the performance of the ACR/EULAR criteria for pSS according to age. Materials and Methods: This medical chart review study included patients with suspected pSS who completed evaluations for pSS. Patients were classified based on age at pSS evaluation: elderly (≥65 years), middle-aged (40–64), and young (<40). The USFR’s optimal thresholds were evaluated using the ROC curve. The diagnostic performances of the USFR and modified ACR/EULAR criteria were compared. Results: In total, 239 pSS patients and 92 patients with idiopathic sicca syndrome were included. The cut-off of USFR ≤0.1 mL/min was irrelevant to age, demonstrating the best sensitivity (44.3–53.0%) and specificity (74.1–90.9%). SGUS had a significantly better AUC than USFR in the young (p<0.01) and middle-aged groups (p<0.01). The middle-aged group demonstrated better diagnostic performance of the ACR/EULAR criteria incorporating SGUS (AUC 0.957) (p<0.01) and criteria replacing USFR with SGUS (AUC 0.957) (p<0.001) compared to the original criteria (AUC 0.916). In the young and elderly groups, adding SGUS to the ACR/EULAR criteria or replacing USFR with SGUS did not significantly increase the AUC. Conclusions: The thresholds of USFR ≤0.1 mL/min was optimal, irrespective of age. Using SGUS can improve diagnostic accuracy of ACR/EULAR criteria by supplementing the USFR, especially in middle-aged patients.